The Von Willebrand Factor A1–Collagen III Interaction Is Independent of Conformation and Type 2 Von Willebrand Disease Phenotype. Issue 1 (6th January 2017) - Machha, Venkata R.; Tischer, Alexander; Moon-Tasson, Laurie; Auton, Matthew
Abstract: The blood von Willebrand factor (VWF) mediates platelet adhesion to injured vessels by sequestering platelets from blood flow and depositing them to collagen and other exposed subendothelial matrix proteins. This process of capturing platelets to facilitate formation of platelet plugs occurs through transient interactions with platelet glycoprotein Ibα via the VWF A1 domain which also binds collagen. Using a conformationally diverse collection of natively folded and mutation-induced misfolded von Willebrand disease (VWD) variants, we test a recently proposed affinity up-regulation hypothesis which states that collagen binding changes the conformation of the A1 domain to a high-affinity GPIbα binding competent state. With surface plasmon resonance (SPR), we present this diversified collection to collagen and quantify the kinetics of association and dissociation to ascertain the conformational selectivity of collagen. With analytical rheology, we quantify real-time platelet pause times and translocation velocities across a Cu 2 + HisTag-chelated and collagen-bound A1 single domain and A1A2A3 tridomain fragment of VWF under shear stress in an ex vivo shear flow microfluidic chamber. In contrast to expected hypothetical outcomes, collagen has limited conformational selectivity for binding A1. A1-collagen binding is independent of gain- or loss-of-function phenotype and under shear stress, platelet translocation pause times on collagen-bound A1A2A3 are either normal or shorter depending on whether A1 is concertedly bound with the A3 domain to collagen. With respect to A1, collagen has an inhibitory role that provides an explanation for the lack of thrombosis in patients with gain-of-function VWD. Graphical Abstract: Highlights: The VWF A1–collagen–GPIbα ternary interaction is not conformationally coupled. VWF A1 binding to collagen is independent of type 2 VWD phenotype. VWF A1 affinity for platelet GPIbα is down-regulated in the presence of collagen.